Transcriptome analysis of Clinopodium gracile (Benth.) Matsum and identification of genes related to Triterpenoid Saponin biosynthesis - Chunmiao Shan; Chenkai Wang; Shengxiang Zhang; Yuanyuan Shi; Kelong Ma; Qingshan Yang; Jiawen Wu (figshare, 2020)
Abstract Background Clinopodium gracile (Benth.) Matsum (C. gracile) is an annual herb with pharmacological properties effective in the treatment of various diseases, including hepatic carcinoma. Triterpenoid saponins are crucial bioactive compounds in C. gracile. However, the molecular understanding of the triterpenoid saponin biosynthesis pathway remains unclear. Results In this study, we performed RNA sequencing (RNA-Seq) analysis of the flowers, leaves, roots, and stems of C. gracile plants using the BGISEQ-500 platform. The assembly of transcripts from all four types of tissues generated 128,856 unigenes, of which 99,020 were mapped to several public databases for functional annotation. Differentially expressed genes (DEGs) were identified via the comparison of gene expression levels between leaves and other tissues (flowers, roots, and stems). Multiple genes encoding pivotal enzymes, such as squalene synthase (SS), or transcription factors (TFs) related to triterpenoid saponin biosynthesis were identified and further analyzed. The expression levels of unigenes encoding important enzymes were verified by quantitative real-time PCR (qRT-PCR). Different chemical constituents of triterpenoid saponins were identified by Ultra-Performance Liquid Chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS). Conclusions Our results greatly extend the public transcriptome dataset of C. gracile and provide valuable information for the identification of candidate genes involved in the biosynthesis of triterpenoid saponins and other important secondary metabolites.
Keywords: Biochemistry; Genetics; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Plant Biology